Numeracy Learning for Children with hearing impairment in Elementary Schools - Khoshimov, Maksud (Universitas Pendidikan Indonesia (UPI), 2024)
This study aimed to explore and understand the learning of arithmetic for children with hearing impairment in elementary schools. This study used a qualitative descriptive method with direct observation in several elementary schools that have Children with hearing impairment children. The results of the study indicate that the use of approaches, methods, and visual media as well as sign language greatly helps Children with hearing impairment children understand the concept of arithmetic. The role of supportive teachers greatly influences the success of mathematics learning for Children with hearing impairment children.